X-y+z=5 -2x-y-z=-6 3x+3y-2z=-5 Solve algebraically.

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

X-y+z=5 -2x-y-z=-6 3x+3y-2z=-5 Solve algebraically.

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

ohhhh...these are a pain in the butt. Very time consuming. here we go... x - y + z = 5 ----- multiply by -1 -2x - y - z = -6 -------------- -x + y - z = -5 (result of multiplying by -1) -2x - y - z = -6 --------------add -3x - 2z = - 11 x - y + z = 5 ---- multiply by 3 3x + 3y - 2z = -5 ---------------- 3x - 3y + 3z = 15 (result of multiplying by 3) 3x + 3y - 2z = -5 ---------------add 6x + z = 10 -3x - 2z = -11 6x + z = 10 ---- multiply by 2 --------------- -3x - 2z = -11 12x + 2z = 20 (result of multiplying by 2) --------------add 9x = 9 x = 1 6x + z = 10 6(1) + z = 10 6 + z = 10 z = 10 - 6 z = 4 x - y + z = 5 1 - y + 4 = 5 5 - y = 5 -y = 0 y = 0 check... -2x - y - z = -6 -2(1) - 0 - 4 = -6 -2 - 4 = -6 -6 = -6 (correct) so x = 1, y = 0, and z = 4
It would probably be easier to use matrices....I am just not too good with those
I was extremely confused, thank you so much for clearing it up for me. This is a huge help. Thank you so much! I'm not too great at matrices, either.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Not the answer you are looking for?

Search for more explanations.

Ask your own question